Implementasi Model Pembelajaran Predict-Observe-Explain Berbasis Masalah Terhadap Keterampilan Proses Sains dan Pemahaman Konsep pada Topik Pencemaran Lingkungan - Susi Marcelina*; Yula Miranda; Soaloon Sinaga; Theo Jhoni Hartanto (Universitas Syiah Kuala, 2022)
Based on the results of observations of learning activities carried out on students in junior high school, it is known that students' science process skills are still relatively low. In addition, students' understanding of concepts on the topic of environmental pollution is still low. The purpose of this study was to describe the effect of predict-observe-explain (POE) based problem model on students’s conceptual mastery and science process skills in learning environmental pollution. The method that was used in this research was pre-experiment and the design was one-group pretest-posttest. Sample of the research were took from one class, namely class VII in a junior high school in Kasongan, Katingan Regency, Central Kalimantan. The instruments used for the research were: (1) achievement test and (2) the science process skills observation sheet. The result showed that there was an improvement in students’ conceptual mastery in learning environmental pollution, indicated by average normalized gain of 0,68. Science process skills of students in environmental pollution topic through POE based problem model gained an average of good category. Therefore, the indicator of science process skills with highest score was the prediction and collecting data aspect, while the lowest score was communicating aspect. From this research can be conclude that applyng the POE based problem model can improve students’ learning outcomes and also give positive effect on students’ science process skills,especially on the topic of environmental pollution